CONVERSATIONAL IMPLICTURE IN INCEPTION MOVIE DIALOGUE - Handrian Nofry Emardos Sigalingging; Lidiman Sahat Martua Sinaga (LINGUISTICA, 2014)
ABSTRACT This study dealt with Conversational Implicature in Inception Movie Dialogue. The objectives of this study were to find out the most dominant types of Conversational Implicature and the meaning of each implicature. This research on this thesis wasconducted by using qualitative descriptive design. The data were taken from Inception movie script that was released in 2010. The data were analyzed and classified into two types of conversational implicature in the procedures namely Generalized Conversational Implicature and Particularized Conversational Implicature.There were 36 conversational implicatures occured in the characters dialogue from Inception movie. The findings indicated that there were Generalized Conversational Implicature 21 (58,33%) and Particularized Conversational Implicature 15 (41,67%). Generalized Conversational Implicature as the most dominant type of conversational implicaturewas used in Inception movie, it means that most of the dialogue could be drawn from linguistic feature and general fact without considering the context.   Keywords:Conversational implicature, Generalized conversational implicature, Particularized conversational implicature